Komunikasi Interpersonal: Memotivasi Kinerja Pemain pada Tim Alter Ego Esports - Agatha, Angelia; Yoedtadi, Moehammad Gafar (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2025)
This study aims to explain the interpersonal communication patterns between coaches and athletes in the Alter Ego esports team in the context of athlete performance motivation. This research uses a qualitative approach with a case study method. The data collection techniques applied were in-depth interviews, non-participant observation, and documentation. The analysis technique used was proposed by Neuman (2014) and consists of three stages, namely Conceptualisation, Coding Qualitative Data, and Outcroppings. The results showed that there was communication between instructors and members, starting from the introduction stage of each character or person. As a result, communication between personal coaches and esports players can motivate players in the team to continue to be enthusiastic. Important elements include communication through specialised groups on messaging platforms and regular meetings. The findings also show that coaches act as leaders who can understand the psychological and emotional aspects of players. Openness in interpersonal communication creates space for players to share their feelings and needs, which in turn, can build trusting relationships. Penelitian ini bertujuan untuk menjelaskan pola komunikasi interpersonal antara pelatih dan atlet dalam tim esports Alter Ego dalam konteks motivasi kinerja atlet. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus. Teknik pengumpulan data yang diterapkan yaitu wawancara mendalam, observasi non-partisipan, dan dokumentasi. Teknik analisis yang digunakan dikemukakan oleh Neuman (2014), terdiri dari tiga tahap yaitu Conceptualization, Coding Qualitative Data, dan Outcroppings. Hasil penelitian menunjukkan bahwa terjalin komunikasi antara instruktur dengan anggota, diawali dari tahap pengenalan dari karakter atau pribadi masing-masing. Hasilnya, komunikasi antar pribadi pelatih dan pemain esports bisa memotivasi pemain dalam tim untuk terus bersemangat. Elemen penting yaitu komunikasi melalui grup khusus di platform pesan dan pertemuan rutin. Hasil temuan juga menunjukkan bahwa pelatih berperan sebagai pemimpin yang dapat memahami aspek psikologis dan emosional pemain. Adanya keterbukaan dalam komunikasi interpersonal menciptakan ruang bagi pemain untuk berbagi perasaan dan kebutuhan, yang pada gilirannya, dapat membentuk hubungan saling percaya.